Aerodynamic Roughness Height of Gravel-covered Plains in the Puna of Argentina - Zimbelman, James R. (2023)
Plains covered by gravel-dominated desert pavement in the Puna of Argentina have an aerodynamic roughness height (or length) z0 of ∼1 cm, likely representing a skimming flow regime above the closely spaced gravel particles. Aerodynamic roughness height locally may transition from that of skimming flow over the gravels to a z0 that includes the effects of obstacles considerably larger than those of the gravel particles alone. Among large (>60 cm tall) megaripples, z0 is elevated beyond that of the gravels alone to values of 2–4 cm. These results represent an analog for an improved understanding of the aerodynamics of gravel-dominated desert pavement and megaripples documented by multiple rovers on Mars.